Women in George Washington's world - Lewis, Charlene M. Boyer, 1965-; Boudreau, George, 1964- (University of Virginia Press, 2022)
"This volume highlights some of the women Washington knew: women who admired and memorialized him; women who provided him love and solace; women who frustrated him; women who worked for or against him. The essays reveal the lives of a diverse group of women, from plantation mistresses to enslaved workers, loyalists and patriots, poets and socialites, as well as mothers, wives, and sisters. Figures discussed include Mary Ball Washington, Martha Washington, Margaret Arnold, Phillis Wheatley, Abigail Adams, Elizabeth Willing Powel, Moll Judge, Ona Judge, Ann Pamela Cunningham, as well as members of the Washington and Custis families and women workers enslaved by them"--